2013
DOI: 10.2113/gssgfbull.184.1-2.119
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of K-feldspar-bearing hydrothermal breccias in the Bouillante geothermal field (Basse Terre – Guadeloupe)

Abstract: International audienceSurficial indicators of recent to present geothermal activity are present around Bouillante (Guadeloupe, French West Indies). Until lately, most mineralogical parageneses identified in this area were typical of low temperature alteration (< 100°C) with the occurrence of dioctahedral aluminous smectites accompanied by zeolites (heulandite-clinoptilolite) ± calcite ± silica ± kaolinite, as an evidence of the cap rock of the geothermal system. Recently, numerous boulders of highly silicified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…High gypsum and pyrite contents are observed in the most altered areas. All of these elements match with a high-temperature hydrothermal paragenesis developed in an epithermal context (Patrier et al, 2013). Verati et al (2016) also demonstrated that the development of this highly hydrothermalized area is controlled by the intersection of two major normal fault systems N090-N110 and N130-140 ( Fig.…”
Section: Hydrothermal Alterationmentioning
confidence: 54%
“…High gypsum and pyrite contents are observed in the most altered areas. All of these elements match with a high-temperature hydrothermal paragenesis developed in an epithermal context (Patrier et al, 2013). Verati et al (2016) also demonstrated that the development of this highly hydrothermalized area is controlled by the intersection of two major normal fault systems N090-N110 and N130-140 ( Fig.…”
Section: Hydrothermal Alterationmentioning
confidence: 54%
“…Several authors have focused their petrographic and geochemical studies on fresh volcanic rocks of the southern active volcanic part of the archipelago, and most of the studies have concentrated further south or near La Soufrière volcano or Bouillante geothermal field providing a revision of the ages of the volcanic formations and the lithological contours Dagain, 1981;Blanc, 1983;Boudon et al, 1989;Samper et al, 2007Samper et al, , 2009Patrier et al, 2013;Verati et al, 2014;Ricci et al, 2017). A recent study has shown the evolution of petrophysical properties from fresh to hydrothermalized volcanic rocks in the volcanic island of Guadeloupe archipelago (Navelot et al, 2018).…”
Section: Guadeloupe In the Lesser Antilles Geological Contextmentioning
confidence: 99%
“…Breccias have been recognized at the surface in the northern Although this rock appears heterogeneous macroscopically (cement and numerous clasts of different colours), its mineralogy is rather homogeneous (Patrier et al 2013). (1) A high-temperature assemblage (adularia + quartz + pyrite); and (2) later parageneses consistent with advanced argillic alterations (mainly jarosite + smectite + illite + illite-smectite mixed layers).…”
Section: Sample Descriptionsmentioning
confidence: 99%
“…part of Bouillante Bay (Patrier et al 2013). All of the breccias are located in a N1708-orientated alteration zone, bounded by the east-west-trending Bouillante Fault and a N508-trending fault.…”
Section: Bo19-k6 Brecciamentioning
confidence: 99%
See 1 more Smart Citation